A high-polarization and fast-response speed photoelectric detector and a preparation method thereof

By leveraging the synergistic effect of PtSe2 and MoS2 layers and the design of the grating layer, a two-dimensional photodetector with high polarization degree and fast response speed in the communication band was achieved, overcoming the stability and response speed limitations in existing technologies and making it suitable for the fabrication method of two-dimensional photodetectors.

CN121001414BActive Publication Date: 2025-12-26HUNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511512099.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-22
Publication Date
2025-12-26
Estimated Expiration
2045-10-22

AI Technical Summary

Technical Problem

Existing two-dimensional polarization-sensitive photodetectors suffer from problems such as high polarization degree but poor stability, or fast response speed but low carrier mobility, which limits their performance in practical applications.

Method used

By utilizing the bandgap-free characteristics of the PtSe2 semimetal to absorb wide-band light, and rapidly separating photogenerated carriers in a short channel of tens of nanometers in the vertical direction between the MoS2 and PtSe2 layers, and combining the grating layer to confine the incident light in the PtSe2 armchair crystal orientation to generate a synergistic effect with the PtSe2 layer, a photodetector structure was designed to achieve high polarization degree and fast response speed.

Benefits of technology

It achieves high polarization degree and fast response speed in the 1310~1560nm communication band, improves the performance of the detector, solves the problem of low processing speed in the existing technology, and improves the yield and stability through a stable fabrication method, which is convenient for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121001414B_ABST
    Figure CN121001414B_ABST
Patent Text Reader

Abstract

The application discloses a photoelectric detector with high polarization degree and fast response speed and a preparation method thereof. The photoelectric detector comprises, from bottom to top, a substrate material, a photovoltaic layer and an electrode layer; the photovoltaic layer comprises, from bottom to top, a Si layer, a SiO2 layer, an Au layer, an aluminum oxide layer, a MoS2 layer, a PtSe2 layer, a MoS2 layer and a grating layer; the Z-shaped crystal direction of the PtSe2 layer is parallel to the grating direction of the grating layer. The detector first determines the crystal phase structure of PtSe2, and then deposits layer by layer through a deposition method, so that the deposition angle of each layer is accurately implemented according to the set requirements, and the transfer process adopts a dry transfer method. The grating integrated vertical sandwich structure detector utilizes the photo-thermal electron effect to perform communication band photoelectric detection, and utilizes the polarization-dependent localized plasmon effect introduced by the grating structure, so that, under the synergistic action, the communication band photoelectric detection with high polarization degree is realized, the detection performance of the detector in the communication band is improved, and the problem of low response speed of the polarization-sensitive photoelectric detector is solved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to a two-dimensional photoelectric detector, in particular to a photoelectric detector with high polarization degree and fast response speed and a preparation method thereof, and belongs to the technical field of photoelectric detection. BACKGROUND

[0002] Polarization-sensitive photoelectric detectors are one of the important research directions in the field of photoelectric detection and imaging in recent years. Because it introduces the ability to perceive the polarization state of light on the basis of traditional light intensity detection, it significantly expands the dimension of optical information acquisition. Polarized light is a physical quantity that reflects the direction of electromagnetic wave vibration, and widely exists in nature and artificial environment. For example, when light is reflected, scattered or transmitted on the surface of an object, its polarization characteristics will usually change predictably, and these changes are closely related to the physical properties of the object, such as the type of material, the surface structure, the thickness and the arrangement direction. Therefore, compared with traditional photoelectric detectors that can only obtain light intensity or spectral information, polarization-sensitive detectors can capture more physical parameters at the same time, thereby providing unique advantages in target identification, imaging contrast enhancement, structure analysis and the like.

[0003] Two-dimensional (2D) materials provide an ideal platform for constructing a new generation of high-performance polarization photodetectors due to their atomic thickness, excellent electronic and optical properties, and strong tunability. Since graphene was successfully exfoliated and its unique photoelectric properties were confirmed, the family of 2D materials has rapidly expanded to include a wide range of members, from metallic graphene, semiconductor transition metal dichalcogenides (e.g., MoS2, WS2), black phosphorus, rhenium dichalcogenides (ReS2), to insulating hexagonal boron nitride, and many others. Some of these 2D materials have inherent crystal structure anisotropy or exhibit strong polarization-selective absorption and photoelectric response under external physical modulation, making them natural candidates for polarization-sensitive detection. Anisotropic 2D materials such as black phosphorus (BP) and ReS2 have lattice structures that are asymmetric in different in-plane directions, resulting in strong differences in absorption coefficients, conductivity, and carrier mobility in different polarization directions. This intrinsic anisotropic response makes it possible to achieve polarization detection without the need for external polarization optics. Compared with traditional polarization detection techniques, polarization photodetectors based on 2D materials have several unique advantages. First, they have extremely small device sizes, are compatible with silicon-based processes, and can be easily integrated into on-chip optoelectronic systems, facilitating the construction of high-density, high-resolution imaging arrays. Second, 2D materials are highly sensitive to external environments, and their photoelectric properties can be modulated through various means such as electric fields, strain, and chemical modification, enabling good dynamic response and reconfigurability of the devices. In recent years, 2D semimetal materials such as palladium diselenide (PdSe2) have further enhanced the performance of polarization-sensitive 2D photodetectors. These 2D semimetal materials naturally exhibit high light response in the visible, near-infrared, and even mid-infrared bands due to the absence of a band gap, broadening the wavelength coverage of the polarization detector and enabling multi-band polarization imaging.

[0004] However, there are still some urgent problems to be solved in current polarization-sensitive 2D photodetectors. The main problems are as follows. First, although photodetectors based on BP exhibit strong polarization degree and response speed, BP is an unstable material whose surface easily reacts with water and oxygen in the air, leading to deterioration of the detection performance. Therefore, there is still a long way to go before practical application. On the other hand, although PdSe2 as a 2D semimetal material has strong stability, its room-temperature carrier mobility is only 158 cm 2 V -1 s -1 , which is much lower than that of graphene (2000 cm 2 V - 1 s -1) also makes the polarization-sensitive photodetector based on PdSe2 response speed limit in the order of microseconds. In this case, the advantage of the polarization-sensitive photodetector can simultaneously capture more physical parameters is difficult to truly play in the face of its low processing speed. SUMMARY

[0005] In view of the problems existing in the prior art, a first object of the present application is to provide a photodetector with high polarization degree and fast response speed. The photodetector is a two-dimensional communication waveband, which is based on the synergistic effect between the layers of each component material, absorbs a wide waveband of light to generate photo-generated carriers through the characteristics of the semi-metal band gap of the PtSe2 layer, the special fast separation of photo-generated carriers in the vertical direction of tens of nanometers between the MoS2 layer, the PtSe2 layer and the MoS2 layer, and the grating layer limits the incident light in the PtSe2 armchair crystal direction and the PtSe2 layer to produce a synergistic effect to amplify the polarization behavior, and finally realizes the technical effect of the photodetector with high polarization degree and fast response speed in the communication waveband of 1310~1560nm, effectively solving the technical problem of low processing speed of the polarization-sensitive two-dimensional photodetector in the prior art.

[0006] A second object of the present application is to provide a preparation method of a photodetector with high polarization degree and fast response speed. The method first determines the crystal phase structure of PtSe2, and then deposits layer by layer through the deposition method, ensures that the deposition angle of each layer is accurately implemented according to the set requirements, and the transfer process adopts dry transfer, so that the obtained detector has the advantages of stable quality, high yield, good stability and the like, and is convenient for large-scale industrial production.

[0007] To achieve the above technical purpose, the present application provides a photodetector with high polarization degree and fast response speed, comprising: the photodetector is sequentially composed of a substrate material, a photovoltaic layer and an electrode layer from bottom to top; the photovoltaic layer is sequentially composed of a Si layer, a SiO2 layer, an Au layer, an aluminum oxide layer, a MoS2 layer, a PtSe2 layer, a MoS2 layer and a grating layer from bottom to top; the Z-shaped crystal direction of the PtSe2 layer is parallel to the grating direction of the grating layer.

[0008] The intrinsic PtSe2 exhibits a small anisotropy (about 1.2) in the communication waveband, and the reason why the Z-shaped crystal direction of the PtSe2 layer is parallel to the grating direction of the grating layer in the present application is to amplify the anisotropic photocurrent detection behavior of the PtSe2 layer by using the grating layer, and the maximum photocurrent anisotropy can reach 5. If they are not parallel, the photodetector constructed may have multiple polar orientations, and the maximum photocurrent anisotropy value is smaller than that of the parallel design.

[0009] As a preferred scheme, the thickness of the MoS2 layer is 0.7 nm to 3 nm, the thickness of the PtSe2 layer is 5 nm to 20 nm, the thickness of the gold layer is 100 nm to 130 nm, and the thickness of the aluminum oxide layer is 100 nm to 120 nm.

[0010] The thicknesses of the materials of the layers are strictly implemented according to the above requirements. If the MoS2 layer is too thick, the channel of the detector will be lengthened, and the vertical carrier transition length will be increased, thereby prolonging the response time of the detector. If the PtSe2 layer is too thin, it will be converted into a semiconductor phase with a band gap of about 1.5 eV, and it will not be able to absorb the incident light signals in the communication band. If the PtSe2 layer is too thick, the absorption will be weakened, the concentration of the photo-generated carriers will be reduced, and the photoelectric detector light response will be reduced. The thicknesses of the gold layer and the aluminum oxide layer are within the above range, and are mainly used to ensure that the resonance wavelength of the grating is within the communication band of 1310 nm to 1560 nm. Therefore, any modification beyond the range will cause the performance of the detector to be reduced, and even the detector cannot be normally used.

[0011] As a preferred scheme, the grating material of the grating layer is one of Au, Ag, Pd, Pt, and Al.

[0012] As a preferred scheme, when the grating material is Au, the thickness of the grating layer is 100 nm to 129 nm.

[0013] As a preferred scheme, the grating period of the grating layer is 1130 nm to 1450 nm, the width of a single grating is 900 nm, and the channel width is 230 nm to 550 nm.

[0014] The above parameters of the grating mainly function in the following aspects: 1. The resonance wavelength is ensured to be within the communication band of 1310 nm to 1560 nm, thereby causing the localized plasmon resonance in the communication band, and improving the detection performance of the detector in the communication band. 2. The integrated grating ensures that the photoelectric detector has different absorption intensities for the transverse magnetic wave and the transverse electric wave of the incident light in the communication band of 1310 nm to 1560 nm, thereby generating a polarization-sensitive photoelectric detection function, and the photoelectric current anisotropy degree is about 6. Therefore, as described above, if the parameters of the grating are not within the above range, the photoelectric detection capability of the photoelectric detector constructed, including the light response and the light response speed, will be obviously reduced, and the photoelectric current anisotropy degree is the same as that of the intrinsic PtSe2, which is only about 1.2.

[0015] As a preferred scheme, the excitation light wavelength of the photoelectric detector is 400 nm to 1560 nm, the intrinsic response speed in the communication band is 1 ps to 5 ps, the actual response speed is 1 ns to 3 ns, the polarization degree is 6, and the response degree is 0.1 A / W to 0.3 A / W.

[0016] The application further provides a preparation method of a photoelectric detector with high polarization and fast response speed, which comprises the following steps: pretreating a Si substrate with SiO2 attached thereon, transferring an Au layer and an aluminum oxide layer onto the substrate by electron beam evaporation and atomic layer deposition in sequence to obtain a modified substrate; transferring MoS2 and PtSe2 onto the modified substrate in sequence after mechanical exfoliation, and performing annealing treatment to obtain a heterojunction precursor; coating the heterojunction precursor with poly methyl-2-methylpropenoat (PMMA), and making an electrode template by electron beam exposure and depositing a metal source-drain electrode to obtain a grating-free detector; obtaining the crystal orientation of PtSe2 in the grating-free detector by using polarized photocurrent, coating PMMA again, and making a grating by electron beam exposure.

[0017] As a preferred solution, the pretreatment process comprises the following steps: cutting the Si substrate with SiO2 attached thereon, and then performing ultrasonic cleaning in propanol, isopropanol and deionized water in sequence for 10-20 min, and then completely drying in a protective atmosphere.

[0018] As a preferred solution, the annealing treatment is performed under the following conditions: a vacuum degree of 0.8*10 -4 Pa~1.2*10 - 4 Pa, a temperature of 150-180℃, and a time of 1-2 h.

[0019] As a preferred solution, after the grating is made, the residual PMMA is removed by solvent immersion.

[0020] As a preferred solution, the solvent is acetone and / or isopropanol.

[0021] As a preferred solution, the metal source-drain electrode is at least one of Cr, Ag, Au, Pt, Cu and Al, and has a thickness of 40-90 nm.

[0022] The detection mechanism of the photoelectric detector is based on the photo-thermal electron effect, and the hot electrons generated in the semi-metal PtSe2 layer cross the Schottky barrier between the PtSe2 layer and the MoS2 layer to inject the MoS2 layer to generate photocurrent. The intrinsic photocurrent response test shows that the injected hot electrons have an ultrafast cooling process of only 2 picoseconds, thus first ensuring the speed of the cooling process after the hot electrons are injected into the MoS2 layer. In addition, the photoelectric detector is designed as a vertical structure, and the injected hot electrons vertically pass through the MoS2 layer with a thickness of only a few nanometers and are immediately collected by the electrode. This process further improves the response speed of the photoelectric detector compared to the lateral carrier crossing. Finally, due to the integration effect of the grating, the electromagnetic waves of the communication band incident light are completely confined in the heterojunction layer. This confinement behavior greatly improves the photocurrent generated by the detector, and thus improves the photoconductivity of the material and reduces the RC time of the device. In combination with the above factors, the grating integrated photoelectric detector designed in the application can achieve a response speed of nanoseconds in the communication band, which is 3 orders of magnitude higher than the conventional technology.

[0023] Compared with the prior art, the beneficial technical effects of the technical scheme of the application are:

[0024] 1) The photoelectric detector provided by the application is a two-dimensional communication band, which is based on the synergistic effect between the layers of each component material, absorbs a wide band of light to generate photo-generated carriers through the band gap-free characteristics of the PtSe2 layer semi-metal, the special fast separation of photo-generated carriers in the vertical direction of the tens of nanometer short channel between the MoS2 layer, the PtSe2 layer and the MoS2 layer, and the grating layer limits the incident light in the PtSe2 armchair crystal direction and the PtSe2 layer to produce a synergistic effect to amplify the polarization behavior, and finally realizes the technical effect of the photoelectric detector with high polarization and fast response speed in the communication band of 1310~1560nm, effectively solving the technical problem of low processing speed of the polarization-sensitive two-dimensional photoelectric detector in the prior art.

[0025] 2) The preparation method provided by the application first determines the crystal phase structure of PtSe2, and then deposits layer by layer through the deposition method, ensuring that the deposition angle of each layer is accurately implemented according to the set requirements, and the transfer process adopts a dry transfer method. The obtained detector has the advantages of stable quality, high yield, good stability and is convenient for large-scale industrial production.

[0026] 3) The grating integrated vertical sandwich structure detector provided by the technical scheme provided by the application utilizes the photo-thermal electron effect to carry out communication waveband photoelectric detection, and simultaneously utilizes the grating structure to introduce the polarization-dependent localized plasmon effect, under the synergistic action of which, not only is the high-polarization photoelectric detection in the communication waveband realized, but also the detection performance of the detector in the communication waveband is improved, and the problem of low response speed of the polarization-sensitive photoelectric detector is solved. According to test, the excitation light wavelength of the photoelectric detector provided by the application is 400nm-1560nm, the intrinsic response speed in the communication waveband is 3ps, the actual response speed is 2ns, the polarization degree is 6, and the response degree is 0.3 A / W. BRIEF DESCRIPTION OF DRAWINGS

[0027] Figure 1 It is a manufacturing process schematic diagram of the detector obtained in embodiment 1 of the application;

[0028] Figure 2 It is a structure schematic diagram of the detector obtained in embodiment 1;

[0029] Among them, Figure 2 a is a detector structure schematic side view, Figure 2 b is a detector structure schematic top view;

[0030] Figure 3 It is a Raman spectrum of PtSe2, MoS2 and MoS2 / PtSe2 / MoS2 heterojunction in the detector obtained in embodiment 1;

[0031] Figure 4 It is a crystal form test diagram of PtSe2 in the detector obtained in embodiment 1;

[0032] Figure 5 It is an electron microscope test result diagram of the detector obtained in embodiment 1;

[0033] Among them, Figure 5 a is an electron microscope test result diagram of the detector obtained in embodiment 1, Figure 5 b is a structure diagram of the grating on the detector obtained in embodiment 1;

[0034] Figure 6 It is a simulation result diagram of the grating limiting effect on 1560nm communication waveband incident light in the detector obtained in embodiment 1;

[0035] Among them, Figure 6 a is a simulation result of the 550nm wide channel grating on the absorption of 1560nm incident light transverse magnetic wave and transverse electric wave in the detector obtained in embodiment 1; Figure 6 b is a magnetic field distribution under the excitation of 1560nm incident light in the detector obtained in embodiment 1;

[0036] Figure 7Current-voltage characteristic curve of the detector obtained in Example 1 on a probe station under excitation of a 1560 nm laser;

[0037] Figure 8 Anisotropic photocurrent test results of the detector obtained in Example 1 under excitation of a 1560 nm laser;

[0038] Figure 9 Time-resolved photocurrent test results of the photodetector obtained in Example 1 under excitation of a 1560 nm laser;

[0039] Figure 10 Simulation results of the 230 nm wide channel grating in the photodetector obtained in Example 2 for absorption of transverse magnetic wave and transverse electric wave of incident light at 1310 nm;

[0040] Figure 11 Anisotropic photocurrent test results of the photodetector obtained in Example 2 under excitation of a 1310 nm laser;

[0041] Figure 12 Actual photocurrent response time of the photodetector obtained in Example 2 tested on a probe station;

[0042] wherein, Figure 12 a is the actual photocurrent turn-on time of the photodetector obtained in Example 2 tested on a probe station, about 48 nanoseconds, Figure 12 b is the actual photocurrent decay time of the photodetector obtained in Example 2 tested on a probe station, about 77 nanoseconds;

[0043] Figure 13 Comparison chart of detection performance of the photodetectors in Example 1 and Example 2 with a van der Waals photodetector;

[0044] wherein, Figure 13 a is the anisotropic photocurrent results of the photodetectors in Comparative Example 1 and Example 2 under excitation of light at different wavelengths, Figure 13 b is the response time and responsivity results of the photodetectors in Comparative Example 1 and the van der Waals photodetector;

[0045] Figure 14 Current-voltage characteristic curve of the photodetector obtained in Comparative Example 1;

[0046] Figure 15 Anisotropic photocurrent response results of the photodetector obtained in Comparative Example 1;

[0047] Figure 16 Simulation results of the 550 nm wide channel grating in Comparative Example 2 for absorption of transverse magnetic wave and transverse electric wave of incident light;

[0048] Figure 17 Anisotropic photocurrent response results of the photodetector in Comparative Example 2. DETAILED DESCRIPTION

[0049] For the purpose of promoting an understanding of the application, the application will be described in greater detail below with reference to specific embodiments thereof. It is however expressly noted that the application is not limited to these embodiments, but can be carried out in many different ways within the scope of the application. Rather, these embodiments are provided in order to make the disclosure of the application as thorough and complete as possible.

[0050] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used in the description of the application herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.

[0051] Example 1

[0052] This embodiment provides a photodetector with high polarization degree and fast response speed, and the preparation process thereof is as shown in Figure 1 Specifically, the preparation process comprises the following steps:

[0053] 1) Cut the Si substrate with 200 nm SiO2 into small pieces of 10 mm x 10 mm, first immerse in acetone, clean in ultrasonic for 15 min, then immerse in isopropanol, clean in ultrasonic for 15 min, and finally immerse in deionized water, clean in ultrasonic for 15 min. After cleaning, blow dry the Si substrate small pieces with nitrogen air gun, and place on a thermal evaporation sample table, evaporate 130 nm Au under a vacuum degree of 2 x 10 -4 Pa, then take out and place the substrate small pieces on an atomic layer deposition sample table, evaporate 120 nm aluminum oxide under a vacuum degree of 1 x 10 -4 Pa, to obtain a modified substrate;

[0054] 2) Mechanically exfoliate MoS2 and PtSe2 in a specific thickness range by using PDMS and Thinkplast tape, then transfer the exfoliated MoS2 and PtSe2 to the modified substrate in sequence to form a MoS2 / PtSe2 / MoS2 sandwich structure, then anneal under a temperature of 180℃ and a vacuum degree of 2 x 10 -4 Pa for 2 hours, and cool to room temperature after annealing, to obtain a heterojunction precursor, wherein the thickness of MoS2 is 2 nm and the thickness of PtSe2 is 15 nm;

[0055] 3) The heterojunction precursor was placed in a spin coater and a 600 nm thick layer of PMMA was spin-coated. Spin-coating was performed continuously at 2000 r / s (low speed) and 4000 r / s (high speed) for 3 seconds and 60 seconds, respectively. The coated sample was then placed on a heating stage at 160°C for 5 minutes to completely dry the PMMA. Electrons were then fabricated on the sample using electron beam lithography, with the electrodes fabricated on the top and bottom layers of MoS2. The sample was then immersed in a developer for 18 seconds to remove the exposed PMMA. Finally, the sample was coated with a 2×10⁻⁶ electron beam lithography solution. -4 5 nm Cr and 50 nm Au were continuously deposited under a vacuum of Pa. The sample stage temperature did not exceed 80°C during the deposition process. The sample was then cleaned and dried in acetone solution and isopropanol to obtain a grating-free detector.

[0056] 4) The anisotropic photocurrent of the gratingless detector was measured using 1560nm excitation light to obtain the Z-shaped crystal phase of PtSe2. Then, PMMA was spin-coated onto the gratingless detector as described in step 3), with a thickness of 400nm. A grating was fabricated on the detector using electron beam exposure, with a grating period of 1450nm and a channel width of 550nm. The grating was parallel to the Z-shaped crystal phase of PtSe2. Finally, the detector was placed on a thermal evaporation sample stage at 2×10⁻⁶ Å. -4 130 nm Au was deposited under a vacuum of Pa, with the temperature not exceeding 80℃ during the deposition process. The sample with the deposited grating was immersed in acetone solution for 2 hours for stripping, and then cleaned and dried sequentially with acetone solution, isopropanol, and dried to obtain the photodetector.

[0057] The structure of the photodetector provided by this invention is as follows: Figure 2 As shown, Raman spectroscopy was performed on PtSe2, MoS2, and MoS2 / PtSe2 / MoS2 sandwich structures, respectively, and the results are as follows. Figure 3 As shown, the constituent materials of its heterojunction structure and its good coupling quality can be determined. The Z-shaped crystal phase of the PtSe2 layer is obtained through... Figure 4 The search is conducted perpendicular to the polarization direction. The resulting detector was also subjected to electron microscopy testing, the results of which are as follows: Figure 5 As shown, through Figure 5 It can be seen that the materials are stacked in an orderly manner, with the grating having a period of 1450nm and a channel width of 550nm, which meets the requirements of the detector parameters.

[0058] This invention simulates the incident light confinement of the aforementioned photodetector, and the results are as follows: Figure 6 As shown, through Figure 6 As can be seen from a, for a transverse magnetic wave of 1560 nm, the grating absorbs nearly 95%, while for a transverse electric wave of 1560 nm, the grating shows almost no absorption; through Figure 6It can be seen that the magnetic field intensity generated by the incident light is almost limited in the heterojunction, indicating the selectivity of the grating to the polarization of the incident light and the effective limiting effect, and also indicating the effectiveness of the improvement of the performance of the grating detector.

[0059] The photoelectric detector is further tested for a series of performances, and the results of the test by applying 1560 nm light are shown in Figure 7 , indicating that the detector has a response to the incident light in the communication band, and the photocurrent can reach 500 nA under a bias of 0.1 V, and the photocurrent generated by the transverse magnetic wave is obviously greater than that generated by the transverse electric wave. The anisotropic photocurrent response results of the detector under 1560 nm light are shown in Figure 8 , in which the 8-shaped photocurrent response reflects the obvious photocurrent polarization direction, and the anisotropy value can reach 6. The time-resolved photocurrent test results of the detector under 1560 nm laser excitation are shown in Figure 9 , and the results show that the intrinsic response time of the detector is as low as 2.8 ps, and this ultrafast photocurrent response is derived from the rapid cooling of the photo-generated carriers in the vertical structure.

[0060] Example 2

[0061] The preparation method of this embodiment is exactly the same as that of example 1, and the difference lies in that the grating period of the grating is 1130 nm and the channel width is 230 nm.

[0062] It can be seen from Figure 10 that by adjusting the grating period, the absorption signal of the incident light can be adjusted at the same time. For a channel width of 230 nm, the absorption of the transverse magnetic wave and the transverse electric wave of the incident light is blue-shifted to 1310 nm, and the absorption of the transverse magnetic wave is as high as 95 percent, while the absorption of the transverse electric wave is only 5 percent. It can be seen from Figure 11 that this type of behavior enables the photoelectric detector of example 2 to have a high anisotropic light response of up to 5 at 1310 nm. Further, it can be seen from Figure 12 that the actual response results of the detector obtained in this embodiment to the incident light of 1310 nm show that the actual photocurrent turn-on and decay times of the photoelectric detector are 48 ns and 77 ns, respectively.

[0063] Figure 13 The performances of the detectors of example 1 and example 2 are summarized and compared with the van der Waals photoelectric detector working in the communication band in the prior art. Among them, Figure 13 a the data of 1560 nm is derived from example 1, and the data of 1200 nm and 1310 nm is derived from example 2, and Figure 13The data in b comes from the results of Example 1 under 1560nm excitation. By comparison, it can be seen that the photodetector provided by the present invention has significant advantages over the photodetectors in the prior art in terms of photocurrent anisotropy, responsivity and response time.

[0064] Comparative Example 1

[0065] Compared with Example 1, the preparation process of this comparative example is completely the same as that of Example 1, except that a detector grating is not set.

[0066] like Figure 14 As shown, when the grating is absent, the detector cannot confine the incident light at 1560 nm, thus the resulting photocurrent is only 100 nA, which is only one-quarter of that of the detector obtained in Example 1. Furthermore, as... Figure 15 As shown, when the grating is absent, the anisotropy of the photocurrent exhibits the intrinsic anisotropy of the PtSe2 layer. Since the anisotropy of PtSe2 is not significant, the anisotropy of the photocurrent is only 1.2–1.3. This test result also demonstrates that by fabricating the grating on the Z-shaped crystal phase of PtSe2 and combining the synergistic effect between the anisotropy of PtSe2 and the anisotropy of the grating, the anisotropy of the photocurrent can be effectively amplified.

[0067] Comparative Example 2

[0068] Compared with Example 1, the preparation process of this comparative example is completely the same as that of Example 1, except that the substrate is a 200 nm SiO2 Si substrate.

[0069] like Figure 16 Simulation results show that when the detector uses a 200 nm SiO2 Si substrate, the grating absorbs less than 5% of the incident light from 800 nm to 1600 nm, exhibiting almost no absorption behavior. This is because the incident light penetrates the silicon dioxide layer and cannot be confined within the heterojunction, thus the grating cannot function. The anisotropic photocurrent response of the detector exhibits the intrinsic behavior of the MoS2 / PtSe2 / MoS2 heterojunction, as shown in the simulation results. Figure 17 As shown, it is only 1.3.

[0070] As can be seen from the above embodiments and comparative examples, the sample can only be successfully prepared in accordance with the technical solution provided by the present invention. If the process requirements of the present invention are not followed, the various properties of the final product will be adversely affected to a certain extent.

Claims

1. A high polarization and fast response speed photodetector, characterized in that: The photoelectric detector comprises, from bottom to top, a substrate material, a photovoltaic layer and an electrode layer; the photovoltaic layer comprises, from bottom to top, a Si layer, a SiO2 layer, an Au layer, an aluminum oxide layer, a MoS2 layer, a PtSe2 layer, a MoS2 layer and a grating layer; the Z-shaped crystal orientation of the PtSe2 layer is parallel to the grating direction of the grating layer. 2.The high-polarization and fast-response photodetector of claim 1, wherein: The thickness of the MoS2 layer is 0.7 nm to 3 nm, the thickness of the PtSe2 layer is 5 nm to 20 nm, the thickness of the Au layer is 100 nm to 130 nm, and the thickness of the aluminum oxide layer is 100 nm to 120 nm. 3.The high-polarization and fast-response photodetector of claim 1, wherein: The grating material of the grating layer is one of Au, Ag, Pd, Pt and Al; when the grating material is Au, the thickness of the grating layer is 100 nm to 129 nm. 4.The high-polarization and fast-response photodetector of claim 1, wherein: The grating period of the grating layer is 1130 nm to 1450 nm, the single grating width is 900 nm, and the channel width is 230 nm to 550 nm.

5. The high polarization and fast response speed photodetector of claim 1, wherein: The excitation light wavelength of the photoelectric detector is 400 nm to 1560 nm, the intrinsic response speed in the communication band is 1 ps to 5 ps, the actual response speed is 1 ns to 3 ns, the polarization degree is 6, and the response degree is 0.1 A / W to 0.3 A / W.

6. The preparation method of the high polarization and fast response speed photodetector according to any one of claims 1-5, characterized in that: The Si substrate with SiO2 attached is pretreated, and then the Au layer and the aluminum oxide layer are transferred to the substrate by electron beam evaporation and atomic layer deposition in sequence to obtain a modified substrate; After the MoS2 and the PtSe2 are mechanically exfoliated, they are transferred to the modified substrate in sequence, and then annealed to obtain a heterojunction precursor; the heterojunction precursor is coated with polymethyl methacrylate, an electrode template is made by electron beam exposure, and a metal source-drain electrode is deposited to obtain a grating-free detector; the crystal orientation of the PtSe2 in the grating-free detector is obtained by using polarized photocurrent, and then PMMA is coated again, and a grating is made by electron beam exposure.

7. The method of claim 6, wherein the method further comprises: depositing a first electrode layer on the substrate; depositing a second electrode layer on the first electrode layer; and depositing a third electrode layer on the second electrode layer. The pretreatment process comprises the following steps: after the Si substrate with SiO2 attached is cut, it is ultrasonically cleaned in propanol, isopropanol and deionized water in sequence for 10 minutes to 20 minutes, and then completely dried in a protective atmosphere.

8. The method of claim 6, wherein the method further comprises: depositing a first electrode layer on the substrate; depositing a second electrode layer on the first electrode layer; and depositing a third electrode layer on the second electrode layer. The annealing conditions are: vacuum degree of 0.8 × 10⁻⁶. -4 Pa ~1.2×10 -4 Pa, temperature 150℃~180℃, time 1h~2h.

9. The method of claim 6, wherein the method further comprises: depositing a first electrode layer on the substrate; depositing a second electrode layer on the first electrode layer; and depositing a third electrode layer on the second electrode layer. After the grating is made, residual PMMA needs to be removed by solvent immersion; the solvent is acetone and / or isopropanol.

10. The method of claim 6, wherein the method further comprises: The metal source-drain electrode is at least one of Cr, Ag, Au, Pt, Cu and Al, and the thickness is 40 nm to 90 nm.

Citation Information

Patent Citations

  • Self-driven photoelectric detector with high polarization sensitivity and preparation method thereof

    CN118553808A

  • Scalable Van Der Waals Superlattices For Absorbers And Emitters

    US20240047592A1